Implementation of Madrasah-Based Management Strategies in Madrasah Aliyah Negeri, Medan City in The Era of The Covid 19 Pandemic - Yusuf Hadijaya; Oda Kinata Banurea; Yulinar Yulinar; Ibnu Hajar; Roniah Situmorang (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The outbreak of the COVID-19 virus has become a global issue that has hit all aspects of life and government, education is two things related to people's lives and government. Education is the place where humans depend to shape civilization and progress, while the government is fully responsible for the implementation of the orders and mandates of the constitution. The purpose of this study was to determine the management implementation strategy based on the Medan City State Madrasah Aliyah during the covid-19 pandemic. This study uses a qualitative approach to the method of library research (library research). The data in this study used data obtained from books, journals, articles, tabloids, newspapers and government-owned data. Data analysis was carried out using content analysis (analyzing data, facts) from the data used in the study. The results of the study found that the CIPP strategy, input-process-output and outcome in the implementation of madrasa-based management carried out by madrasas during the covid 19 period by internalizing the situation and environment of the madrasa condition as well as assessing the strength of the organization's resources (vision, mission, goals, human resources, students, curriculum, infrastructure, financing).